2015
DOI: 10.1021/jacs.5b01740
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Lewis Acid Catalysis in Intramolecular [2 + 2] Photocycloaddition Reactions: A Mechanistic Comparison between Representative Coumarin and Enone Substrates

Abstract: The intramolecular [2 + 2] photocycloaddition of three 4-(alk-4-enyl)coumarins and three 1-(alk-4-enoyl)-2,3-dihydropyridones was studied in the absence and in the presence of Lewis acids (irradiation wavelength λ = 366 nm). Spectral and kinetic data were collected for the respective parent compounds with a pent-4-enyl and a pent-4-enoyl chain. For the substrates with a methyl group in cis- or trans-position of the terminal alkene carbon atom (hex-4-enyl and hex-4-enoyl substitution), the stereochemical outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
79
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 78 publications
8
79
0
3
Order By: Relevance
“…Whereas the enantioface differentiation by the Lewis acid occurs in analogy to that with the coumarins, the reaction mechanisms differ significantly. In the presence of a Lewis acid, a rate enhancement was observed for the coumarins, whereas the reactions of enones were retarded 22. The quantum yields are consistent with these observations.…”
Section: Activation By Lewis Acidssupporting
confidence: 83%
See 1 more Smart Citation
“…Whereas the enantioface differentiation by the Lewis acid occurs in analogy to that with the coumarins, the reaction mechanisms differ significantly. In the presence of a Lewis acid, a rate enhancement was observed for the coumarins, whereas the reactions of enones were retarded 22. The quantum yields are consistent with these observations.…”
Section: Activation By Lewis Acidssupporting
confidence: 83%
“…The cycloaddition did not occur stereospecifically, and in a later study, it was shown that the aforementioned reasons for the catalytic effect of a Lewis acid also applied to this reaction 22. The quantum yield Φ of the reaction 10 a → 11 a amounts to 2×10 −3 without a Lewis acid, whereas Φ =0.09 in the presence of chiral Lewis acid 12 .…”
Section: Activation By Lewis Acidsmentioning
confidence: 92%
“…This observation is in agreement with earlier studies that reported on a similar behavior for coumarins and other α,β‐unsaturated β‐aryl‐substituted carbonyl compounds 6. The reason for the intensity increase is a bathochromic shift of the strong short‐wavelength ππ* absorption 5c. As a consequence of the high absorption cross‐sections of such Lewis acid/enone complexes, [2+2] photocycloaddition reactions can be rendered enantioselective in the presence of a chiral Lewis acid 5, 7, 8…”
mentioning
confidence: 99%
“…30,31 Following the previous works regarding the thermal cycloaddition reactions catalyzed by a chiral Lewis acid, [32][33][34][35] Bach and his coworkers applied chiral oxazaborolidine-AlBr 3 based Lewis acid catalyst (1 see scheme 1) to enable the enantioselective intramolecular [2+2] PCA of coumarin (2) and a typical enone substrate, i.e., 5,6-dihydro-4-pyridones (3). [36][37][38][39] As shown in scheme 1, the stereochemical PCA products 4 and 5 have been obtained with the satisfied yield (~0.84) and high enantioselectivity (82~90% ee) in the presence of catalyst 1 when the unselective background reaction was noticeably suppressed at high catalyst loadings (typically ~50 mol %). However, the mechanistic courses of coumarins were found to be totally different from the PCA reaction of dihydropyridones.…”
mentioning
confidence: 81%
“…36,39 In comparison with the uncatalyzed background reactions, the reaction rates were accelerated for the cycloaddition reaction of coumarins but slowed down in the presence of a chiral Lewis acid of dihydropyridones. 36,39 All these experimental observations indicate that it is a challenging issue to understand the regulatory mechanism mediated by the chiral Lewis acid and to effectively suppress the unselective background reaction. To achieve a general strategy for controlling racemic background reactions, an innovative approach was developed in Yoon's group 7,40-46 by the introduction of one more transition 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 metal complex that is able to trigger the photoredox reaction regulated by single-electron transfer.…”
mentioning
confidence: 99%